Same/not same - Lopičić, Vesna (Primerjalna književnost, 2016)
The article discusses Karen Joy Fowler%s 2013 novel We Are All Completely Beside Ourselves, primarily in the context of the growing demands for nonhuman animal rights/liberation. The general thrust of the novel is in keeping with animal rights activism and the animal studies' critical examination of the human/animal relations.
Keywords: Fowler, Karen Joy, 1950-; American literature; ameriška književnost; človek in žival; odnos do živali; pravice živali; humanism; humanizem; antropocentrizem; nasilje; jezik; Language; science; znanost